News Framing of the Rohingya Crisis Settlement: a Study on Aljazeera and BBC - Osama Kanaker; Mohamed Oklah Abughazlih; Mohamed Battour; Ihab Ahmed Awais; Khalaf Mohammed Tahat (Centre for Language Studies and Generic Development, UMK, 2024)
Non-Indexed Publication